Looking for the women in Baron and Taylor's (1969) Educational administration and the social sciences - Fuller, Kay (Taylor & Francis, 2014)
A search for women in Baron and Taylor's (1969) Educational administration and the social sciences [London: The Athlone Press] using feminist poststructural discourse analysis (FPDA) has revealed a changing discourse about gendered educational administration over the course of 50 years. Whilst few women are featured in the text itself, citations of women's writing surface the historical contributions of women as headmistresses and public servants. Women who have cited the text since its publication have challenged gendered theory and academic writing conventions. FPDA is used to explore the gendered educational administration discourse through the intertextuality of academic writing. Fluctuations between powerfulness and powerlessness are revealed depending on the socio-political context and women's circumstances.